Nephrotoxicity of Sodium Benzoate and Ameliorating Role of Ephedra alata Aqueous Extract on Some Biochemical Parameters in Male Rats - Mohammed Bouleefah; Nuhay Alkeelani; Ibrahim Eldurssi; Ebtesam Gheth; Mabroka Hamad (AlQalam Journal of Medical and Applied Sciences, 2025)
A common preservative, sodium benzoate, is used in a variety of foods, such as salads, fruit juices, jams, and carbonated drinks, as well as in the pharmaceutical industry to preserve liquid medications. Ephedra alata is utilized for its anti-cold and anti-hay fever, and asthmatic effects. The purpose of this study is to evaluate Ephedra alata aqueous extract’s ability to protect against sodium benzoate-induced kidney injuries, including urea, creatinine, uric acid, sodium, potassium, and chloride in the blood sera in male rats. In this study, twenty male albino rats weighing between 195 and 300 g were employed. The rats were divided into 4 groups, each with 5 rats. Animals in the control group were given distilled water orally every day for two weeks. In the group of sodium benzoate, rats were administered 100 mg/kg/b. w. of sodium benzoate orally daily for two weeks. Ephedra alata group, included rats that were administered aqueous extract of Ephedra alata daily at a dose (1g/kg b.w.) for two weeks. Animals received an oral dose of ephedra aqueous extract with sodium benzoate for two weeks. Twenty-four hours after the two-week treatment period ended, the rats from the reference and experimental groups were weighed and sacrificed by jugular decapitation. Their blood samples were collected for biochemical investigation, including urea, creatinine, uric acid, sodium, potassium, and chloride in the blood sera. According to the study’s findings, when compared to the control group, none of the groups’ serum urea, creatinine, uric acid, Na+, K+2, and Cl levels changed significantly after two weeks; however, the sodium benzoate rats’ potassium levels significantly decreased. In conclusion, the study’s findings support sodium benzoate’s little harmful effects on the kidneys and no effects of ephedra when it is administered as a protective agent.